CUL-2(LRR-1) and UBXN-3/FAF1 drive replisome disassembly during DNA replication termination and mitosis - Sonneville, Remi (Nat Cell Biol, 2017)
Replisome disassembly is the final step of DNA replication in eukaryotes, involving the ubiquitylation and CDC48-dependent dissolution of the CMG helicase (Cdc45-MCM-GINS). Using Caenorhabditis elegans early embryos and Xenopus egg extracts, we show that the E3 ligase CUL-2(LRR-1) associates with the replisome and drives ubiquitylation and disassembly of CMG, together with the CDC-48 co-factors UFD-1 and NPL-4. Removal of CMG from chromatin in frog egg extracts requires CUL2 neddylation, and our data identify chromatin recruitment of CUL2(LRR1) as a key regulated step during DNA replication termination. Interestingly, however, CMG persists on chromatin until prophase in worms that lack CUL-2(LRR-1), but is then removed by a mitotic pathway that requires the CDC-48 co-factor UBXN-3, orthologous to the human tumour suppressor FAF1. Partial inactivation of lrr-1 and ubxn-3 leads to synthetic lethality, suggesting future approaches by which a deeper understanding of CMG disassembly in metazoa could be exploited therapeutically.